Nurse managers' support of fundamental care in the hospital setting. An interpretive description of nurse managers' experiences across Australia, Denmark, and New Zealand. (7th January 2022) - Mudd, Alexandra; Feo, Rebecca; Voldbjerg, Siri L.; Laugesen, Britt; Kitson, Alison; Conroy, Tiffany
Abstract: Aims: To explore the role of ward‐based nurse managers in supporting nurses to undertake high‐quality fundamental care. Design: A qualitative study guided by the principles of interpretive description. Reported in accordance with Consolidated Criteria for Reporting Qualitative Research (COREQ). Methods: Nurse managers in three urban, publicly funded hospitals in Australia, Denmark and New Zealand, were invited to participate in group interviews to discuss how they support fundamental care in their clinical areas. Six group interviews were conducted between February 2017 and March 2020 involving 31 participants. Results: Six interrelated themes were identified: Difficulty expressing how to support the nurse—patient relationship; Establishing expectations for care delivery without clear strategies for how this can be achieved; Role modelling desired behaviours; Significance of being present to support care quality; The importance of engaging and supporting staff in their work; and Recognizing the challenges of prioritizing care needs. Conclusion: This study indicates that nurse managers are not universally clear in explaining how they support their staff to provide fundamental care. If fundamental care is not clearly understood and communicated in the nursing team, then there are risks that fundamental care will not be prioritized, with potential negative consequences for patient care. Nurse managers may benefit from additional resources and guidance to help them to support fundamental care delivery in their clinical areas. Impact: Previous research exploring fundamental care and missed care highlights the importance of the role of the nurse manager in influencing nursing care. This study demonstrates that though nurse managers have a passion for supporting their staff to deliver fundamental care, clear strategies to achieve this are not always evident. This study suggests that scholarship around leadership to promote and facilitate fundamental care is crucial to improving nursing practice and patient outcomes.